2004
DOI: 10.1007/s10522-004-2575-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent alterations in mitochondrial enzymes in cortex, striatum and hippocampus of rat brain ? potential role of L-Carnitine

Abstract: Mitochondria link the energy -- releasing activities of electron transport and proton pumping with the energy conserving process of oxidative phosphorylation to form ATP. A declined mitochondrial performance has been generally observed during aging. In the present investigation, the activities of tricarboxylic acid cycle enzymes such as isocitrate, alpha-ketoglutarate, succinate and malate dehydrogenases and electron transport complexes I-IV were measured in mitochondria isolated from brain regions like cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In the literature, few studies were performed to evaluate the effect of L-CAR on learning and memory deficits induced by different pathological conditions. L-CAR exhibits antioxidant properties [26,55], and several studies showed that carnitine exhibits neuroprotective effects in aging animals [53]. A study showed that aged rats treated with L-CAR exhibited improvement in the levels of SOD, catalase, and GPx [46].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, few studies were performed to evaluate the effect of L-CAR on learning and memory deficits induced by different pathological conditions. L-CAR exhibits antioxidant properties [26,55], and several studies showed that carnitine exhibits neuroprotective effects in aging animals [53]. A study showed that aged rats treated with L-CAR exhibited improvement in the levels of SOD, catalase, and GPx [46].…”
Section: Discussionmentioning
confidence: 99%
“…OXPHOS in the presence of substrates feeding electrons through complexes I and II decrease in the brain from aged compared to young rats [25]. The activities of complex I [25, 26, 72, 73], complex I+III [21, 74] and complex IV [21, 26, 7278], and the content in cytochromes c and aa 3 [25] also were reported to decrease during aging.…”
Section: Evidence For the Protective Effect Of Acetylcarnitine Agamentioning
confidence: 99%
“…Preservation of mitochondrial function is important for maintaining overall health during aging. In order to protect the mitochondria against respiration-linked oxidative stress, and to preserve the genomic and structural integrity of these energyproducing organelles dietary supplementation with antioxidants, such as vitamins, N-acetyl cysteine, DL-a-lipoic acid and L-carnitine has been suggested (Chow 1991;Arivazhagan et al 2001;Haripriya et al 2004). The heart is one of the organs, which highly depends on oxidative energy generated in mitochondria, by fatty acid b-oxidation, respiratory electron chain and oxidative phosphorylation (Cadenas and Davies 2000;Marin-Garcia and Goldenthal 2002;Arai et al 2003).…”
Section: Introductionmentioning
confidence: 99%